An online energy-tracking-based approach for fault-identification applies to the NUGS. (July 2020) - Tong, Ning; Lin, Xiangning; Sui, Quan; Wang, Zhixun; Jin, Neng; Li, Feiyu; Li, Zhengtian
Highlights: The authors found the distribution rules of fault-induced high-frequency energy. An online approach is put forward to track the origin of the principal component energy to determine the faulted feeder. RTDS-based close-loop test platform is established to justify the proposed method. The performance of the proposed method is discussed in detail. Abstract: Fault identification for the neutral un-effectively grounded distribution systems (NUGS) has long been an unsolved problem since conventional zero-sequence protective relays cannot trip the single-line-to-ground fault. Moreover, few branch-feeders are equipped with zero-sequence current monitors, whereas existing fault-identification methods that not relying on the zero-sequence current measurement are facing problems regarding speed and sensitivity. To solve this problem, the distribution characteristics of the high-frequency energy of the faulted phase within the entire NUGS is firstly analyzed. Then, the principal-component-energy (PCE) is employed to represent the high-frequency energy related to the occurrence of the single-line-to-ground fault. Finally, an online tracking approach is proposed to find the origin of the PCE. To assess the performance of the proposed method, massive fault scenarios are studied on a closed-loop RTDS test platform. Test results indicate that the proposed method is capable of online application independent of zero-sequence current measurement and data synchronization. Also, the sensitivity is high enough to cover a thousand Ohms' fault resistance.